Ethno-Medicinal, Phytochemical and Antimicrobial Studies of Euphorbia tirucalli L. - Ashwani Kumar, Bhuvaneshwar Upadhyay*, K.P. Singh and (Journal of Phytology, 2010)
SUMMARY Present study exposed various claims about the medicinal properties of Euphorbia tirucalli L., used by the indigenous people of Rajasthan to cure rheumatism, Skin disorders, Cough and other ailments. This plant was assessed for ethnopharmacological screenings, phytochemical analysis and antimicrobial screenings which also include anti-HIV activity, so as to validate the efficacy of indigenous herbal medicine. In the present study antimicrobial activity of the crude alcoholic extracts of leaf and stem of E. tirucalli against the known enteric pathogens was carried out. Anti-HIV screening activity was carried out using HIV Protease colorimetric Assay.Â Low MIC exhibited by the extract against S. aureus is of great significance in the healthcare delivery system, since it could be used as an alternative to orthodox antibiotics in the treatment of infections caused by these microbes, especially as they frequently developing resistance to known antibiotics. Key words: Alkaloids, Triterpenes, Antimicrobial activity, anti-Carcinogenic, Anti-HIV <span style="font-weight: normal; font-size: 7pt; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Bhuvaneshwar Upadhyay et al. Ethno-Medicinal, Phytochemical and Antimicrobial Studies of Euphorbia tirucalli L. Â J. Phytol 2/4 (2010) 65-77.